Auditor Knowledge Deficiency, Work Experience, and Internal Control Systems as Determinants of Audit Disclosure Quality: A Mixed-Method Inquiry - Jannah, Nurlaila Masirotul; Anwar, Choirul; Buchdadi, Agung Dharmawan (Journal of International Accounting, Taxation and Information Systems, 2026)
In an increasingly complex business environment, the quality of audit disclosures has become a critical concern for stakeholders, regulators, and the accounting profession, as weaknesses in auditor competence and organizational systems continue to undermine the reliability of financial reporting. This study aims to analyze the effect of auditor knowledge deficiency, auditor work experience, and internal control systems on the quality of audit disclosure in Public Accounting Firms. This research employs a mixed method approach with an explanatory sequential design, where the quantitative stage is conducted first through questionnaires distributed to 45 auditors and audit managers, followed by a qualitative stage using in-depth interviews to strengthen the interpretation of the findings. Quantitative analysis is done using the SEM-PLS method to examine the relationships between variables, while qualitative analysis is used to explore the processes and conditions influencing audit disclosure quality. The results indicate that auditor knowledge, work experience, and internal control systems have a positive and significant effect on audit disclosure quality. Auditor knowledge plays a role in determining the accuracy and relevance of disclosed information, work experience enhances professional judgment and the preparation of audit narratives, and internal control systems ensure the availability of accurate and traceable data. The integration of quantitative and qualitative findings shows that audit disclosure quality is formed through the synergy between auditor competence and organizational system effectiveness. This study contributes to understanding the factors affecting audit disclosure quality and highlights the importance of improving auditor competence and strengthening internal control systems in modern auditing practices.